The New "Brain" Concept of Learning. - Hart, Leslie A. (Education Digest, 1978)
This article presents new insights into the nature and process of learning with emphasis on the role of human brain in the process. One must be prepared to set aside a good deal of "educational psychology," that predates most brain research and is of little practical value. A few aspects of the brain, as it can be comprehended today, may explain the ineffectiveness of standard classroom teaching for many students. The brain is now seen to be by no means the stimulus-response device presented in various behaviorist theories. The processing depends little on what or how the teacher has presented, and greatly on the total, previous, stored experience in that particular brain. Thus, the standard presentation, lecture, recitation, and discussion that take up most of the instructional time in classrooms cannot be expected to produce learning in any reliable way. One basic technical aspect of the brain is that all never channels carry information not like an electric current but by pulses. Awareness of program learning calls for new materials designed for the purpose. Few exist, but they can readily be created or adapted to program building.